Export process management of Huu nghi food joint stock Company - evaluation and Improvement - Tran, Thi Huong Quynh (2020)
Integration in the context of supply chain management is believed as the foundation to achieve more flexible supply chain. The complexity of export processes challenges in integration world, and also widens the need for effective export process management. The prior literature also affirmed the significance of export performance, export process management. In order to gain more understandings regarding this issue, this research is to introduce an overview of the export, export process, and how to monitor it well. In this research, I go to details in stages of export process, the challenges of export process management. Besides, I also assess export process of an enterprise, Huu Nghi Food Joint Stock Company (HNF) as a particular example. From the proposed problems, I give recommendations and measures for HNF export process management.